In vitro Evaluation of ASCs and HUVECs Co-cultures in 3D Biodegradable Hydrogels on Neurite Outgrowth and Vascular Organization - Rocha, Luís A.; Gomes, Eduardo D.; Afonso, João L.; Granja, Sara; Baltazar, Fatima; Silva, Nuno A.; Shoichet, Molly S.; Sousa, Rui A.; Learmonth, David A.; Salgado, Antonio J. (Frontiers in Cell and Developmental Biology, 2020)
Vascular disruption following SCI decisively contributes to the poor functional recovery prognosis facing patients with the condition. Using a previously developed gellan gum hydrogel to which the adhesion motif GRGDS was grafted (GG-GRGDS), this work aimed to understand the ability of ASCs to impact vascular organization of HUVECs and how this in turn affects neurite outgrowth of dorsal root ganglia (DRG) explants. Our data shows that culturing these cells together lead to a synergistic effect as showed by increased stimulation of neuritogenesis on DRG. Importantly, HUVECs were only able to assemble into vascular-like structures when cultured in the presence of ASCs, which shows the capacity of these cells in reorganizing the vascular milieu. Analysis of selected neuroregulatory molecules showed that the co-culture upregulated the secretion of several neurotrophic factors. On the other hand, ASCs and ASCs+HUVECs presented a similar profile regarding the presence of angiotrophic molecules herein analyzed. Finally, the implantation of GG-GRGDS hydrogels encapsulating ASCs in the chick chorioallantoic membrane (CAM) lead to increases in vascular recruitment towards the hydrogels in comparison to GG-GRGDS alone. This indicates that the combination of ASCs with GG-GRGDS hydrogels could promote re-vascularization in trauma-related injuries in the CNS and thus control disease progression and induce functional recovery.